Safety of high-dose doripenem in adult patients with cystic fibrosis. (June 2016) - Strawbridge, Seth; Nailor, Michael D.
Background: High doses of β-lactam antibiotics have been advocated for acute pulmonary exacerbations caused by Pseudomonas aeruginosa in patients with cystic fibrosis (CF) secondary to high minimum inhibitory concentrations (MIC) of the infecting organisms. Some β-lactam antibiotics have increased elimination in CF patients. This case series examines the safety of high-dose doripenem (HDD), 2 g intravenously every 8 hours, which is 4 times the labeled dose, in CF patients. Methods: This was a retrospective, single site, chart review of all CF patients given HDD during a 3-year period. Adverse events were prospectively defined using labeled definitions within the package insert and the medical literature. A standard case report form was used to collect demographic details, antibiotic lengths of therapy and adverse events. Results: A total of 17 patients (9 males), with a median age of 24 years, contributed 43 unique visits and 382 HDD exposure days. Mean duration of inpatient doripenem use was 8.9 days. Concurrent antibiotics were common, with a median number of additional antibiotics per admission of three. The median number of adverse effects documented was two. The most common adverse event was anemia, which was identified in 41 of 43 visits, but was present on admission in 31 instances. One patient developed leukopenia for 1 day, but returned to normal without dose adjustment. There were three instances of Clostridium difficile infection. One patient was documented to have an allergic reaction that led to discontinuation, but was ultimately rechallenged without adverse effect. Other common adverse events were gastrointestinal in origin. No other possible adverse effects led to discontinuation of the drug. Conclusions: In adult patients with CF, HDD in combination with other antibiotics did not lead to adverse effects necessitating discontinuation. HDD should be considered in this selected patient population, particularly when high MIC organisms are identified.